Transition metal doped basic group difunctional CO2 adsorbent, preparation method and application of transition metal doped basic group difunctional CO2 adsorbent

By doping the transition metal into Ni@Na2ZrO3, a transition metal-doped base bifunctional CO2 adsorbent is formed, which solves the problem of poor circulation stability of the existing Na-based CO2 adsorbent under high temperature conditions, and achieves efficient CO2 adsorption and cycle stability, reducing costs.

CN119869435AActive Publication Date: 2025-04-25CHINA PETROLEUM & CHEMICAL CORP +2

Patent Information

Application Number
CN202411901230.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-04-25
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing Na-based CO2 adsorbent has poor circulation stability under high temperature conditions and is relatively expensive, making it difficult to meet the application needs of sustainable development.

Method used

The transition metal is doped into Ni@Na2ZrO3 by co-precipitation method to form a transition metal-doped base bifunctional CO2 adsorbent, which promotes the formation of in-situ pores and channels, and improves the CO2 adsorption performance and cycle stability of the adsorbent.

Benefits of technology

It significantly improves the adsorption amount and circulation stability of CO2, reduces the preparation cost, and improves the exposed area of ​​active sites and the microstructure complexity of the adsorbent.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869435A_ABST
    Figure CN119869435A_ABST
Patent Text Reader

Abstract

The invention discloses a transition metal doped base bifunctional CO2 adsorbent, a preparation method and application thereof. The transition metal doped base bifunctional CO2 adsorbent comprises a base bifunctional material and transition metal. The preparation method comprises the following steps: weighing transition metal, Ni, Na and Zr sources, mixing and dissolving in deionized water, stirring to form a uniform solution, weighing a precipitant, dissolving in deionized water, adding into the mixed system after complete dissolution, and stirring to form a uniform solution; stirring and precipitating the mixed system in a constant-temperature water bath kettle, drying the precipitate, calcining the obtained solid powder, and grinding into powder to obtain the transition metal doped base bifunctional CO2 adsorbent. The preparation method of the transition metal doped basic group difunctional CO2 adsorbent material is simple, a coprecipitation method preparation process is adopted, transition metal is doped into Ni-Na2ZrO3, formation of in-situ holes and pore channels is promoted, and the exposed area of active sites of the adsorbent is increased; meanwhile, the formation of lattice defects in unit cells is promoted, the surface energy of the crystal face of the material is changed from the physical dimension of a solid, and the adsorption capacity and cycling stability of CO2 are improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of gas purification, and in particular relates to a transition metal-doped base bifunctional CO2 adsorbent, a preparation method and application thereof. Background Art

[0002] CO2 emitted from the combustion of fossil fuels is the main cause of global warming, and its contribution rate has exceeded 60%. Adding a decarbonization device after the flue gas desulfurization and denitrification system to capture and separate carbon dioxide in the flue gas is widely considered to be one of the most effective ways to achieve carbon dioxide emission reduction in the short term. Compared with the absorption flue gas decarbonization technology, the adsorption technology can significantly reduce the regeneration energy consumption and avoid problems such as equipment corrosion. However, the actual flue gas flow is large, the CO2 concentration is low, and the composition is complex, which poses great challenges to the specific surface area, adsorption capacity, adsorption rate, selectivity, chemical stability, etc. of CO2 capture materials.

[0003] The selection of adsorbent materials is a key factor in the high-temperature solid adsorption method. The high-temperature solid adsorbents reported so far mainly include Ca-based adsorbents, Li-based adsorbents and Na-based adsorbents. Although calcium-based adsorbents represented by CaO have a high CO2 capture and adsorption capacity, due to the severe sintering of CaO under high temperature conditions, its high-temperature carbon absorption performance is greatly attenuated, and in the long run it cannot meet the application needs of sustainable development. Although Li-based adsorbents have both high cycle stability and adsorption capacity, the high cost of Li sources makes their application cost too high, and they are not suitable for large-scale applications at present. In contrast, Na-based adsorbents can just overcome the application bottlenecks of the first two. They have both low raw material costs and excellent cycle carbon absorption stability. They are an adsorbent material with great application prospects. Therefore, the development of efficient Na-based CO2 adsorbents has far-reaching practical significance.

[0004] Chinese patent CN118267966A discloses a method for preparing a performance-enhanced Na2ZrO3-based CO2 adsorbent. The CO2 adsorbent prepared according to the invention can only maintain the cyclic CO2 adsorption performance in a low-concentration CO2 atmosphere, and the CO2 adsorption capacity decreases significantly after the number of cycles reaches 4.

[0005] To this end, in order to solve the technical problems existing in the above-mentioned background technology, the present invention provides a method for preparing a transition metal-doped base bifunctional CO2 adsorbent material, which can effectively improve the adsorption amount and cycle stability of CO2. Summary of the invention

[0006] The object of the present invention is to provide a transition metal-doped base bifunctional CO2 adsorbent, a preparation method and application thereof, so as to solve the problems raised in the above-mentioned background technology.

[0007] To achieve the above object, the present invention provides the following technical solution: a transition metal-doped base bifunctional CO2 adsorbent, comprising a base bifunctional material and a transition metal.

[0008] Preferably, the base bifunctional material is Ni@Na2ZrO3.

[0009] Preferably, in any of the above solutions, the transition metal and Ni account for 8-12% of the total weight of the material.

[0010] In any of the above schemes, preferably, the mass ratio of the transition metal to Ni is 1:(0.8-1.2).

[0011] Preferably, in any of the above schemes, the Na2ZrO3 accounts for 88-92% of the total weight of the material, wherein the molar ratio of Na to Zr is 1:(0.3-0.5).

[0012] A method for preparing a transition metal-doped base bifunctional CO2 adsorbent comprises the following steps:

[0013] S1: Weigh a certain amount of transition metal, Ni, Na, and Zr sources, mix and dissolve in deionized water, and stir magnetically to form a uniform solution;

[0014] S2: Weigh a certain amount of precipitant and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath and maintained for 6h to 8h;

[0015] S3: placing the precipitate in a drying oven for 12 to 14 hours to dry out the water therein;

[0016] S4: placing the obtained solid powder in a muffle furnace, calcining and grinding it into powder to obtain a transition metal-doped base bifunctional CO2 adsorbent.

[0017] In any of the above schemes, preferably, in step S1, the transition metal includes a combination of one or more of Co, Fe, Mn, Cu, and Zn.

[0018] Preferably, in any of the above schemes, in step S1, the stirring speed is 1000-1500 rpm / min.

[0019] In any of the above schemes, preferably, in step S2, the precipitant is a combination of one or more of urea, sodium hydroxide or sodium carbonate.

[0020] Preferably, in any of the above schemes, in step S2, the ratio of the precipitant to the total molar amount of the metal element is 6-10.

[0021] Preferably, in any of the above schemes, in step S2, the temperature in the water bath is 60-80°C.

[0022] In any of the above schemes, preferably, in step S3, the drying temperature is 100-120°C.

[0023] Preferably, in any of the above schemes, in step S4, the calcination process is to first heat the temperature to 350-450°C and maintain for 2 hours, and then heat the temperature to 630-680°C and calcine for 6 hours.

[0024] Application of a transition metal-doped base bifunctional CO2 adsorbent in flue gas CO2 capture and conversion process.

[0025] Technical effects and advantages of the present invention:

[0026] 1. The preparation process of the adsorbent of the present invention is simple, the cost is low, and the modification effect is significant. Through the co-precipitation method, the transition metal is doped into Ni@Na2ZrO3, which promotes the formation of in-situ pores and channels, making the final adsorbent microstructure more complex, increasing the exposed area of ​​the active sites of the adsorbent, and improving the CO2 adsorption performance of the adsorbent.

[0027] 2. The present invention promotes the formation of lattice defects in the unit cell by using transition metal doping, changes the surface energy of the material crystal surface from the dimension of solid physics, and further changes the adsorption energy and charge density difference of CO2 adsorption, thereby significantly improving the adsorption amount and cycle stability of CO2. BRIEF DESCRIPTION OF THE DRAWINGS

[0028] Figure 1 is a SEM image of the adsorbent of Example 1 of the present invention.

[0029] Figure 2 This is the CO2 cycle adsorption diagram of the adsorbent in Example 1 of the present invention.

[0030] Figure 3 It is a comparison chart of the CO2 adsorption capacity of the adsorbents in Example 1 of the present invention and Comparative Examples 1, 2, and 3.

[0031] Figure 4 It is the SEM picture of the adsorbent of Comparative Example 2 of the present invention.

[0032] Figure 5 It is the SEM picture of the adsorbent of Comparative Example 3 of the present invention. DETAILED DESCRIPTION

[0033] The specific embodiments of the present invention are further described below in conjunction with the accompanying drawings. It should be noted that the description of these embodiments is used to help understand the present invention, but does not constitute a limitation of the present invention. In addition, the technical features involved in the various embodiments of the present invention described below can be combined with each other as long as they do not conflict with each other.

[0034] Embodiment 1:

[0035] Weigh 40 g of cobalt acetate, 39.95 g of nickel acetate, 300 g of sodium nitrate and 326.48 g of zirconium oxynitrate, mix and dissolve in deionized water, and stir magnetically to form a uniform solution;

[0036] Weigh 2480 g of urea and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath at 70° C. and maintained for 6 hours.

[0037] The precipitate was placed in a drying oven at 120°C for 12 h to dry out the moisture;

[0038] The obtained solid powder was placed in a muffle furnace, first heated to 400°C and maintained for 2 hours, then heated to 650°C and calcined for 6 hours. After calcination, it was ground into powder to obtain the transition metal-doped base bifunctional adsorption material S1.

[0039] Embodiment 2:

[0040] Weigh 43.8 g of ferric acetate, 39.95 g of nickel acetate, 300 g of sodium nitrate and 326.48 g of zirconium oxynitrate, mix and dissolve in deionized water, and stir magnetically to form a uniform solution;

[0041] Weigh 2480 g of urea and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath at 70° C. and maintained for 6 hours.

[0042] The precipitate was placed in a drying oven at 120°C for 12 h to dry out the moisture;

[0043] The obtained solid powder was placed in a muffle furnace, first heated to 400°C and maintained for 2 hours, then heated to 650°C and calcined for 6 hours. After calcination, it was ground into powder to obtain the transition metal-doped base bifunctional adsorption material S2.

[0044] Embodiment 3:

[0045] Weigh 39.1 g of manganese acetate, 39.95 g of nickel acetate, 300 g of sodium nitrate and 326.48 g of zirconium oxynitrate, mix and dissolve in deionized water, and stir magnetically to form a uniform solution;

[0046] Weigh 2480 g of urea and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath at 70° C. and maintained for 6 hours.

[0047] The precipitate was placed in a drying oven at 120°C for 12 h to dry out the moisture;

[0048] The obtained solid powder was placed in a muffle furnace, first heated to 400°C and maintained for 2 hours, then heated to 650°C and calcined for 6 hours. After calcination, it was ground into powder to obtain the transition metal-doped base bifunctional adsorption material S3.

[0049] Embodiment 4:

[0050] Weigh 45.12 g of copper acetate, 39.95 g of nickel acetate, 300 g of sodium nitrate and 326.48 g of zirconium oxynitrate, mix and dissolve in deionized water, and stir magnetically to form a uniform solution;

[0051] Weigh 2480 g of urea and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath at 70° C. and maintained for 6 hours.

[0052] The precipitate was placed in a drying oven at 120°C for 12 h to dry out the moisture;

[0053] The obtained solid powder was placed in a muffle furnace, first heated to 400°C and maintained for 2 hours, then heated to 650°C and calcined for 6 hours. After calcination, it was ground into powder to obtain the transition metal-doped base bifunctional adsorption material S4.

[0054] Embodiment 5:

[0055] Weigh 39.1 g of manganese acetate, 39.95 g of nickel acetate, 300 g of sodium nitrate and 326.48 g of zirconium oxynitrate, mix and dissolve in deionized water, and stir magnetically to form a uniform solution;

[0056] Weigh 1632 g of sodium hydroxide and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath at 70° C. and maintained for 6 hours;

[0057] The precipitate was placed in a drying oven at 120°C for 12 h to dry out the moisture;

[0058] The obtained solid powder was placed in a muffle furnace, first heated to 400°C and maintained for 2 hours, then heated to 650°C and calcined for 6 hours. After calcination, it was ground into powder to obtain the transition metal-doped base bifunctional adsorption material S5.

[0059] Comparative Example 1:

[0060] The method is the same as Example 1, except that cobalt acetate is not added during the preparation of the adsorbent, and finally adsorbent D1 is obtained.

[0061] Comparative Example 2:

[0062] The method is the same as Example 1, except that the adsorbent is not calcined in stages during the calcination process, but is directly calcined at 650° C. for 6 h, and finally adsorbent D2 is obtained.

[0063] Comparative Example 3:

[0064] The method is the same as Example 1, except that Ni component is added during the preparation of the adsorbent, and finally catalyst D3 is obtained.

[0065] Performance evaluation of base adsorption materials

[0066] The CO2 adsorbents prepared in Examples 1 to S and Comparative Examples 1 to 3 were tested for cyclic CO2 adsorption performance. The adsorption conditions were: adsorption temperature 700°C, adsorption time 25 min, and atmosphere 30 vol.% CO2 and 70 vol.% N2. Specific evaluation data are shown in Table 1 below:

[0067] Table 1

[0068] Adsorbent <![CDATA[CO2 adsorption capacity (g adsorbent / g CO2)]]> S1 0.31 S2 0.26 S3 0.25 S4 0.18 S5 0.26 D1 0.11 D2 0.19 D3 0.21

[0069] It can be seen from the data in Table 1 that the CO2 adsorbent prepared by this method can show good adsorption performance under the conditions of adsorption temperature of 700°C, adsorption time of 25min, and atmosphere of 30vol.% CO2 and 70vol.% N2, especially the adsorption amount and cycle stability of Example 1 are better.

[0070] Since the transition metal Co was not added in Comparative Example 1, it was found that the CO2 adsorption amount was significantly lower during use; Comparative Example 2 used the same transition metal as Example 1, but since the staged calcination method was not adopted during the calcination process, the surface microstructure of the adsorbent was destroyed, resulting in a significant decrease in the CO2 adsorption amount.

[0071] In addition, in Comparative Example 3, no Ni component was added, and the adsorbent structure was quite different from that in the embodiment, so the CO2 adsorption capacity was relatively low.

[0072] At the same time, the adsorbent S1 prepared by this method was found through SEM testing to have a large number of mesopores and micro-macropores combined with a thin layer structure on the surface of the adsorbent, and the surface was rough; the S1 adsorbent was continuously cycled for 10 times and it was found that the CO2 adsorption amount remained stable and did not show a downward trend. The adsorbents prepared in Example 1 and the comparative example were compared for 25 minutes, and it was found that the CO2 of Example 1 was significantly higher than that of the comparative example.

[0073] In summary, it can be seen that the embodiment of the present invention not only has a simple preparation process, but also doping transition metals into Ni@Na2ZrO3 promotes the formation of in-situ pores and channels, making the final adsorbent microstructure more complex, increasing the exposed area of ​​the adsorbent active sites, and improving the CO2 adsorption performance and cycle life of the adsorbent.

[0074] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technician familiar with this profession can make some changes or modifications to equivalent embodiments of equivalent changes by using the methods and technical contents disclosed above without departing from the scope of the technical solution of the present invention. However, any simple modification, equivalent change and modification made to the above embodiments according to the technical essence of the present invention without departing from the content of the technical solution of the present invention still fall within the scope of the technical solution of the present invention.

Claims

1. A transition metal-doped base bifunctional CO2 adsorbent, characterized in that: include Base bifunctional materials and transition metals.

2. The transition metal-doped base bifunctional CO2 adsorbent according to claim 1, characterized in that: The base bifunctional material is Ni-Na2ZrO3.

3. The transition metal-doped base bifunctional CO2 adsorbent according to claim 2, characterized in that: The transition metal and Ni account for 8-12% of the total weight of the material.

4. The transition metal-doped base bifunctional CO2 adsorbent according to claim 3, characterized in that: The mass ratio of the transition metal to Ni is 1:(0.8-1.2).

5. The transition metal-doped base bifunctional CO2 adsorbent according to claim 1, characterized in that: The Na2ZrO3 accounts for 88-92% of the total weight of the material, wherein the molar ratio of Na to Zr is 1:(0.3-0.5).

6. A method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to any one of claims 1 to 5, characterized in that: The following steps are involved: S1: Weigh a certain amount of transition metal, Ni, Na, and Zr sources, mix and dissolve in deionized water, and stir magnetically to form a uniform solution; S2: Weigh a certain amount of precipitant and dissolve it in deionized water. After it is completely dissolved, add it to the above mixed system. The mixed system is stirred and precipitated in a constant temperature water bath and maintained for 6h to 8h; S3: placing the precipitate in a drying oven for 12 to 14 hours to dry out the water therein; S4: placing the obtained solid powder in a muffle furnace, calcining and grinding it into powder to obtain a transition metal-doped base bifunctional CO2 adsorbent.

7. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S1, the transition metal includes one or more combinations of Co, Fe, Mn, Cu, and Zn.

8. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S1, the stirring speed is 1000-1500 rpm / min.

9. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S2, the precipitant is a combination of one or more of urea, sodium hydroxide or sodium carbonate.

10. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S2, the molar ratio of the precipitant to the total amount of the metal element is 6-10.

11. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S2, the temperature in the water bath is 60-80°C.

12. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S3, the drying temperature is 100-120°C.

13. The method for preparing a transition metal-doped base bifunctional CO2 adsorbent according to claim 6, characterized in that: In step S4, the calcination process is to first raise the temperature to 350-450°C and maintain for 2 hours, and then raise the temperature to 630-680°C and calcine for 6 hours.

14. Use of the transition metal-doped base bifunctional CO2 adsorbent according to any one of claims 1-5 and 7-13 in the process of capturing and converting flue gas CO2.

Citation Information

Patent Citations

  • Gas trapping member and vacuum heat insulation equipment

    CN111217540A

  • Hydrocarbon reforming hydrogen production reaction device and method for preventing CO poisoning

    CN111960381A

  • Zirconium-doped layered double hydroxide film electrocatalyst as well as preparation method and application thereof

    CN115433963A

  • Performance-enhanced Na2ZrO3-based CO2 adsorbent as well as preparation method and application thereof

    CN118267966A

  • Catalyst for exhaust purification, device and filter for exhaust purification, and method for production of the catalyst

    JP2016123937A

Cited By

  • Performance-enhanced Na2ZrO3-based CO2 adsorbent as well as preparation method and application thereof

    CN118267966A